ANALISIS KETERAMPILAN PENGELOLAAN KELAS PADA PEMBELAJARAN TEMATIK TERHADAP KESULITAN BELAJAR KELAS III SD SWASTA ABDI SUKMA - Witri Evalia Kuswara; Nila Lestari (STKIP Subang, 2024)
The aim of this research is to analyze classroom management skills in thematic learning on learning difficulties in class III of Abdi Sukma private elementary school and to describe the teacher's ability to manage the class according to learning topics, as well as supporting and limiting factors in classroom management. This research uses qualitative research methods with a case study type. The type of research used in this research is quantitative research. The data analysis method used by the author in analyzing existing problems is the descriptive data analysis method. The research subjects are researchers and homeroom teachers for class III of Abdi Sukma Private Elementary School, Medan Johor District and the objects in this research are students of Abdi Sukma Private Elementary School, Class III of Abdi Sukma Private Elementary School. Medan Johor District. The instruments used in this research are questionnaires, observations, interviews, documentation. Data validity by carrying out, Source Triangulation, Method or Technique Triangulation, Data Analysis Techniques, Data Collection, Data Reduction, Data Presentation or Data Display, Data Verification. The results of the research show that class teachers and teachers accompanying students who experience learning difficulties show inappropriate attitudes (social). Low student academic achievement (Academic). Difficulty making new understanding (Metacognition). Students are slow in processing something (Processing speed). Students find it difficult to interpret what they feel, hear and see (Perception). Students are less attentive and less focused on learning (Attention). There are too many less useful activities that students do so it is difficult to remember the lesson material (Memory). There are 2 factors that cause students to experience learning difficulties, namely internal and external factors. This research suggests that teachers can be more varied in implementing learning. Schools should pay attention to what things can influence the learning process. Future researchers can use the results of this research as a basis for subsequent research